Predictive Value of Microalbuminuria, Systolic Blood Pressure, and Serum Uric Acid Levels for Preeclampsia/Severe Preeclampsia in Gestational Hypertensive Patients - Ha Hong Nguyen; Le Thi Nguyen; Phuc Hoang Tran; Kien Trung Nguyen; An Viet Tran; Son Kim Tran; Chau Minh Tran; Toan Hoang Ngo (Clinical and Experimental Obstetrics & Gynecology)
Background: Preeclampsia is one of the most prevalent hypertensive disorders during pregnancy, leading to various issues that have an adverse impact on both the mother and the fetus. Study to evaluating several biomarkers to predict preeclampsia/severe preeclampsia in gestational hypertensive patients. Methods: We conducted a cross-sectional analysis study of 126 pregnant women with gestational hypertension. The assessment of microalbuminuria, systolic blood pressure, and serum uric acid levels linked to incidents of preeclampsia/severe preeclampsia (after a 3-month follow-up) was carried out utilizing the receiver operating characteristic (ROC) curve. Results: Among the 126 pregnant women with gestational hypertension studied, 26 patients (20.6%) developed preeclampsia/severe preeclampsia during the 3-month follow-up period. In the logistic regression analysis, variables including systolic blood pressure, creatinine, serum uric acid, and microalbuminuria were identified as independent risk factors predicting preeclampsia/severe preeclampsia in gestational hypertensive patients (p < 0.05). Microalbuminuria, with a cut-off point of 126.25 mg/L, demonstrated a sensitivity of 96.2%, specificity of 96%, and an area under the curve of 0.981. Regarding systolic blood pressure, the cut-off threshold, sensitivity, and specificity were 155 mmHg, 65.4%, and 91%, respectively. Serum uric acid, with a threshold of 352.7 μmol/L, showed a sensitivity of 92.3% and a specificity of 67%, and was found to be a significant predictor of preeclampsia/severe preeclampsia in patients with gestational hypertension (p < 0.001). Conclusions: In gestational hypertensive patients, the assessment of microalbuminuria, serum uric acid, and monitoring of blood pressure indices is recommended to facilitate early prediction of the onset of preeclampsia/severe preeclampsia.